A Hermeneutic Approach to Necip Fazıl’s “Mirrors Cut My Way” and Functions of Poetry Language - Hilal Akça (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
The most important feature of literary texts is their multi-layered structure and the possibility of multiple interpretations. Hermeneutics is one such method of interpreting and explaining a text. Initially, it was only used in the interpretation of religious and legal texts and in the explanation of literary texts since the 18th century. However, the perspective of classical and modern hermeneutics on the concepts of understanding and interpretation is different. According to modern hermeneutics, the interpreter applies the meaning of the text to his own language, imagination, and life. Following this method, the poem of Necip Fazıl’s “Mirrors Cut My Way” will be analyzed with the analysis method developed based on the philosophical interpretation idea. Concepts such as image, metaphor, and symbol, which compose the features and functions of poetic language, will be evaluated in linguistic and cultural contexts. The functions of the language of poetry will be made visible by illustrating how Necip Fazıl’s “quest” metaphor, which constitutes the main axis of the art of poetry, supports a structure that is suitable for multiple meanings with its religious, philosophical, psychological, historical, mystical, and metaphysical layers.